Further Evaluation Of Aerodynamic Characteristics Of The Aero 3 Trainer Aircraft Wing - Thirunavakarasu, Prakash (2000)
The MD3-160 basic aerobatic trainer aircraft manufactured by Syarikat Malaysian Explosives Aviation (SMEAv) , a subsidiary of SME , had its first flight in Malaysia in 1994 and has been a reliable trainer aircraft for the Royal Malaysian Air Force (RMAF). As the aircraft was designed and first manufactured in Switzerland, a substantial part of the design documentation is available in the German language. Reports on the performance characteristics of the wing is of particular importance because future work involving All Up Weight (AUW) increase and 4 seater versions of the aircraft will require a sound understanding of wing aerodynamics. The existing wing aerodynamics report by Max Datyler (MDB), the originator of the above mentioned aircraft design does not provide sufficient justification on the aerodynamics of the wing. Work done here seeks to reestablish undocumented sections of the above mentioned report and reproduce a report in English detailing the important areas detailed hereunder. This thesis provides calculations leading to the derivation of the wing airfoil contour and certain aerodynamic characteristics. An estimated AUW of a 4 seater aircraft was used as a basis to determine the new critical wing load cases. Chordwise and spanwise pressure distributions have been derived for both the existing and the proposed 4 seater aircraft, both manually and by using dedicated software. The 2-dimensional and 3-dimensional lift curve slope, maximum lift coefficient and the stalling angle is also derived together with a general discussion on the overall viability of the current wing to be used for an increased AUW or a 4 seater aircraft.